A History of Abortion Access in the Maritime Provinces, 1969–2024 - O’Byrne, Nicole C.; Hamill, Elise C. (Journal of New Brunswick Studies / Revue d’études sur le Nouveau-Brunswick, 2026)
This paper examines the legal history of abortion access in Nova Scotia, New Brunswick, and Prince Edward Island over the past five decades. Since the federal government partially decriminalized abortion in 1969, provincial governments have introduced various legislative and regulatory measures pursuant to their constitutional responsibility for health under section 92 of The Constitution Act, 1982.1 In this paper, we focus on the legislative and regulatory approaches to accessing abortion in the Maritime provinces. The legislative history and jurisprudential framework are not solely decisive in this complex area of social policy; however, they provide an essential perspective for understanding the current debate over access to abortion services.